Implementasi Pembelajaran Proyek Berbasis Sosial Kemasyarakatan dalam Mengembangkan Sosial Emosional Anak Usia 5 sampai 6 Tahun Di PAUD KB Harapan Dita - Zani Rahmah, Rosalinda; Karta, I Wayan; Sativa, Filsa Era (Mataram University, 2025)
This study aims to determine the effect of community-based social project learning on the socio-emotional development of children aged 5–6 years at PAUD KB Harapan Dita. The research employed a quantitative approach using a quasi-experimental method with a One Group Pretest–Posttest Design. The research subjects consisted of 15 children in Group B. Data were collected through observation and documentation, using a socio-emotional development observation sheet as the instrument. The results showed that the average pretest score was 73.00%, while the posttest score increased to 79.93%, reflecting an improvement of 6.93%. The paired sample t-test revealed a significance value of 0.000 (p < 0.05), indicating a significant effect of community-based social project learning on the socio-emotional development of children aged 5–6 years. Social project activities such as cleaning the mosque yard, planting flowers, and visiting the sick contributed positively to the enhancement of children’s cooperation, responsibility, and empathy.